White Collar Crime Dalam Persepektif Islam - Ade Sakinah Pane; Handayani Harahap; Sahlan Sahlan (Pusat Riset dan Inovasi Nasional, 2024)
The word white collar crime is a term used to refer to people who have a high social status who commit legal violations in a legitimate job position. In Indonesian, white collar crime is defined as white collar crime/tie crime.